2021
DOI: 10.3390/bios11030087
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free and Highly-Sensitive Detection of Ochratoxin A Using One-Pot Synthesized Reduced Graphene Oxide/Gold Nanoparticles-Based Impedimetric Aptasensor

Abstract: Ochratoxin A (OTA) primarily obtained by the genera aspergillus and penicillium, is one of the toxic substances for different organs and systems of the human body such as the kidney, liver, neurons and the immune system. Moreover, it is considered to cause tumors and fetal malformation even at a very low concentration. Fast and sensitive assay for detection of OTA at ultralow levels in foods and agricultural products has been an increasing demand. In this study, a new label-free electrochemical biosensor based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The 3D-rGO/AuNPs nanocomposites were synthesized through a one-pot hydrothermal reduction process according to our previous article [15]. Briefly, 20 mg of GO nanosheets were dissolved in 10 mL of water under ultrasonic treatment for 2 h to form 2 mg/mL of GO suspension.…”
Section: Synthesis Of 3d-rgo/aunps Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3D-rGO/AuNPs nanocomposites were synthesized through a one-pot hydrothermal reduction process according to our previous article [15]. Briefly, 20 mg of GO nanosheets were dissolved in 10 mL of water under ultrasonic treatment for 2 h to form 2 mg/mL of GO suspension.…”
Section: Synthesis Of 3d-rgo/aunps Nanocompositesmentioning
confidence: 99%
“…The mixture was then centrifuged and the supernatant was collected as the original stock solution. It was found that the original stock solution of real samples possessed a huge matrix effect [15,31], resulting in false results. Thus, the rice and oat sample stock solutions were diluted 10-fold for accurate electrochemical analysis.…”
Section: Validation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D-rGO/Au NPs were synthesized using a one-pot method coated on a glassy carbon electrode, providing a large binding site for the -SH-modified aptamer through unique Au-S connections. Yasmin and colleagues used electrochemical impedance spectroscopy (EIS) for testing and showed a linear response from 1 pg/mL to 10 ng/mL with a limit of detection (LOD) of 0.34 pg/mL for OTA detection in red wine samples [34]. The plentiful presence of carboxyl groups in the CQDs provided strong bonding of aptamers on the surface of CQDs with π-π interactions [35].…”
Section: Aptamer-functionalized Cnmsmentioning
confidence: 99%